USE OF BaNaY FAUJASITE ZEOLITE–BASED BIMETALLIC COMPOSITE CATALYSTS FOR DEEP BIOFUEL PURIFICATION AND SELECTIVE XYLENE SEPARATION - Davlatova, Odina (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The use of biofuels in electricity and heat supply is a key pathway for conserving fossil resources and lowering environmental burdens. In particular, converting agricultural residues into biofuels can enhance energy security in Uzbekistan and many other countries. This study prioritises deep purification of biofuels using zeolites, selective recovery of high‑purity xylenes and other aromatics, and acceleration of reaction rates via zeolite‑based bimetallic composite catalysts (Ni, Fe, and Ni–Fe systems) to improve overall fuel quality. Zeolites are crystalline sorbent–catalysts with molecularly ordered microporous frameworks whose importance in biomass upgrading (pyrolysis, gasification) has grown markedly; nevertheless, questions remain about their specific functions, selectivity limits, and stability in biomass‑derived vapours. Here, we set out the scientific basis for zeolite‑assisted pyrolysis and subsequent upgrading, and present a detailed assessment of the adsorption behaviour of ortho‑, meta‑, and para‑xylene on BaNaY (FAU) zeolite. The results are compared using adsorption isotherms, differential heats of adsorption, and entropy metrics, enabling a thermodynamic‑selectivity analysis that supports the use of FAU‑type sorptive polishing together with Ni/Fe and Ni–Fe catalytic functionalities in advanced biomass‑to‑fuel processes.